Odd-skipped labels a group of distinct neurons associated with the mushroom body and optic lobe in the adult Drosophila brain. - Levy, P.; Larsen, C. (Journal of Comparative Neurology, 2013)
Olfactory processing has been intensively studied in Drosophila melanogaster. However, we still know little about the descending neural pathways from the higher order processing centers and how these connect with other neural circuits. Here we describe, in detail, the adult projections patterns that arise from a cluster of 78 neurons, defined by the expression of the Odd-skipped transcription factor. We term these neurons Odd neurons. By using expression of genetically encoded axonal and dendritic markers, we show that a subset of the Odd neurons projects dendrites into the calyx of the mushroom body (MB) and axons into the inferior protocerebrum. We exclude the possibility that the Odd neurons are part of the well-known Kenyon cells whose projections form the MB and conclude that the Odd neurons belong to a previously not described class of extrinsic MB neurons. In addition, three of the Odd neurons project into the lobula plate of the optic lobe, and two of these cells extend axons ipsi- and contralaterally in the brain. Anatomically, these cells do not resemble any previously described lobula plate tangential cells (LPTCs) in Drosophila. We show that the Odd neurons are predominantly cholinergic but also include a small number of ?-aminobutyric acid (GABA)ergic neurons. Finally, we provide evidence that the Odd neurons are a hemilineage, suggesting they are born from a defined set of neuroblasts. Our anatomical analysis hints at the possibility that subgroups of Odd neurons could be involved in olfactory and visual processing.